1999
DOI: 10.1029/1999gl900469
|View full text |Cite
|
Sign up to set email alerts
|

Linking the 10Be continental record of Lake Baikal to marine and ice archives of the last 50 ka: Implication for the global dust‐aerosol input

Abstract: Abstract. We present here a 1øBe profile from the continental sediments of Lake Baikal (the world's largest fresh water lake), which, for the first time, shows the = 40 ka løBe enhancement and a pattern that strongly matches those from the marine and ice records for the last 50 ka. This finding provides a new horizon for global and regional correlation of continental archives. Additionally, our VADM-predicted løBe production confirms and further strengthens a common global cause (geomagnetic field intensity) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Two peaks in 36 Cl concentration at 32 ka and ~35-39 ka are seen in the Summit GRIP ice core (Baumgartner et al 1997b(Baumgartner et al , 1998Wagner et al 2000b). Enhanced 10 Be concentrations have also been observed in sedimentary records from Lake Baikal at 40 ka (Aldahan et al 1999), the Caribbean Sea at 35-40 ka , the Gulf of California at 32 and 43 ka (McHargue et al 1995), and the Mediterranean Sea at 34±3 ka (Cini Castagnoli et al 1995).…”
Section: Paleointensity As a Correlation Toolmentioning
confidence: 84%
See 1 more Smart Citation
“…Two peaks in 36 Cl concentration at 32 ka and ~35-39 ka are seen in the Summit GRIP ice core (Baumgartner et al 1997b(Baumgartner et al , 1998Wagner et al 2000b). Enhanced 10 Be concentrations have also been observed in sedimentary records from Lake Baikal at 40 ka (Aldahan et al 1999), the Caribbean Sea at 35-40 ka , the Gulf of California at 32 and 43 ka (McHargue et al 1995), and the Mediterranean Sea at 34±3 ka (Cini Castagnoli et al 1995).…”
Section: Paleointensity As a Correlation Toolmentioning
confidence: 84%
“…A climatic origin for some the features in the ice cores was ruled out by examining δ 18 O and sulfate ion concentrations, which showed no evidence of a change in precipitation or atmospheric transport of aerosols coinciding with the 10 Be spikes . In a series of papers, Aldahan and coworkers (Aldahan et al , 1999 demonstrated that variations in sediment lithology and sediment grain size can also lead to enhancement of 10 Be content in sediments, and thus far only the ~32 ka feature and ~39 ka feature appear to have a robust, global signal.…”
Section: Paleointensity As a Correlation Toolmentioning
confidence: 98%
“…This peak is not anti-correlated with δ 18 O ice , though the oxygen isotopes values are low, as is often seen during a glacial period, but suggesting an influence of changes in the activity either of the Sun or of the Earth's magnetic field. Since there is evidence in the 10 Be record for association of high concentration during excursions in the Earth's magnetic field12131415, we hypothesize that the peak might be due to a magnetic excursion such as the Iceland basin (IB) excursion around 180–190 kyr BP1617 or the Jamaica/Pringle fall at 205–215 kyr BP1718. Assuming this ice to be around 200 kyr old, about 10% of the original 10 Be concentration would have decayed which would put the original concentration at approximately 2.5 × 10 4  atoms/g ice .…”
Section: Discussionmentioning
confidence: 99%
“…Polar ice cores reliably record 10 Be fluxes over time at high latitudes [e.g., Finkel and Nishiizumi , 1997]; however, these fluxes can differ dramatically from those at lower latitudes because of atmospheric production and mixing processes [e.g., Heikkilä et al , 2009]. Deep‐sea and most lake sediment records are filtered by drainage basin and biologic processes making delivery rates over time difficult to deconvolve accurately [e.g., Aldahan et al , 1999]. Because deposition rates of meteoric 10 Be to the soil surface change over time and space as rainfall, dust flux, and geomagnetic shielding all vary, performing additional geologic calibrations at a variety of latitudes, in different precipitation regimes, and over different integration times will improve the accuracy and precision of surface process studies using this isotope system.…”
Section: Discussionmentioning
confidence: 99%